2021
DOI: 10.1002/acr2.11239
|View full text |Cite
|
Sign up to set email alerts
|

Social Distancing, Health Care Disruptions, Telemedicine Use, and Treatment Interruption During the COVID‐19 Pandemic in Patients With or Without Autoimmune Rheumatic Disease

Abstract: Background We aimed to compare concerns, social distancing, health care disruptions, and telemedicine use in patients with autoimmune rheumatic disease (ARD) and non‐ARD and to evaluate factors associated with immunomodulatory medication interruptions. Methods Patients in a multistate community rheumatology practice network completed surveys from April 2020 to May 2020. Adults with common ARD (rheumatoid arthritis, spondyloarthritis, systemic lupus erythematosus) or non‐ARD (gout, osteoarthritis, osteoporosis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Reductions in DMARD use have been reported in other studies 17 19–22. Our results regarding 2020 suggest marked changes compared with 2019 (decreasing starts and increasing stops of bDMARDs/tsDMARDs); such changes in dispensations could be affected by treatment hoarding or prioritisation of use for COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…Reductions in DMARD use have been reported in other studies 17 19–22. Our results regarding 2020 suggest marked changes compared with 2019 (decreasing starts and increasing stops of bDMARDs/tsDMARDs); such changes in dispensations could be affected by treatment hoarding or prioritisation of use for COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…We previously found that patients who avoided office visits early in the pandemic were the most likely group to stop a DMARD, but that patients who replaced these missed visits with telemedicine were less likely to stop a DMARD (11,16). In the current study, avoiding office visits at baseline was associated with increased future interruptions in DMARD use, but there was no association between telemedicine and interruptions in DMARD use.…”
Section: Discussionmentioning
confidence: 99%
“…telemedicine) [6]. Telemedicine was rapidly adopted as a potential solution to provide care to rheumatology patients in the setting of the coronavirus disease 2019 (COVID-19) pandemic [7 ▪ ,8,9 ▪▪ ], and several models have been suggested to address access, health equity, and quality of care barriers [10,11]. Within rheumatology, telemedicine provides an opportunity to address several barriers to adequate care including workforce shortages [12], reaching patients in rural or medically underserved areas [13] or those reluctant to present for in-person care because of the risks of contracting COVID-19 [14].…”
Section: Introductionmentioning
confidence: 99%